2020
DOI: 10.3390/coatings10030286
|View full text |Cite
|
Sign up to set email alerts
|

Composite Ferroelectric Coatings Based on a Heat-Resistant Polybenzoxazole Polymer Matrix

Abstract: The polycondensation of 5,5-methylene bis(2-aminophenol) and the mixture of diamines 5,5-methylene bis(2-aminophenol) and 4,4-(hexafluoroisopropylidene)dianiline (molar ratio 0.8:0.2) with isophthaloyl dichloride was used to synthesize a new heat resistant binder of the composites for microelectronics: poly(o-hydroxyamide) (POA) and poly(amido-o-hydroxy amide) (POA-F). The thermal stability of synthesized polymer coatings, as well as based on them photosensitive compositions with a naphthoquinondiazide photose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, magnetization (magnetic dipole), ferroelectric and piezoelectric effects have been neglected. These require ferrohydrodynamic theory [79], ferro-electro-mechanical models [80] for modelling e.g. lead-magnesium-niobate (PbMgN) and piezo-electric fluid-solid models [81] for simulating e.g.…”
Section: Stimulatedmentioning
confidence: 99%
“…However, magnetization (magnetic dipole), ferroelectric and piezoelectric effects have been neglected. These require ferrohydrodynamic theory [79], ferro-electro-mechanical models [80] for modelling e.g. lead-magnesium-niobate (PbMgN) and piezo-electric fluid-solid models [81] for simulating e.g.…”
Section: Stimulatedmentioning
confidence: 99%
“…[1] It was shown that the thermal stability of polymer materials is affected by the content, structure and compatibility of their constituents, method of their synthesis and processing, bond energy of polymer structure, type of the bonds (covalent or noncovalent), degree of unsaturation, functional groups, molecular weight, branch degree, crosslinking and crystalline degree. [1][2][3][4][5][6][7][8][9][10][11] The following relationship between structure of polymers and their thermal stability was reported: Macromolecules with stiff chains are more thermostable than the ones of the same class with flexible chains. Aromatic and heterocyclic polymers are more thermostable than the linear and fatty cyclic hydrocarbon ones; the absence of hydrogen atoms in macromolecules reduces thermo-oxidative degradation of polymers; polymers having stiff ladder figure chains are high thermostable since polymer chains are not degraded while scission of a single bond occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymer-based materials have attracted attention for flexible electronic devices. Their flexibility, low cost, fast discharge rate, low dielectric loss, and simple manufacturing process make it possible to apply them to capacitors [5][6][7][8][9][10]. Among them, polyvinylidene fluoride (PVDF) shows a relatively high permittivity (k = 5-10), superhydrophobicity with low surface energy, remarkable mechanical strength, and chemical resistance.…”
Section: Introductionmentioning
confidence: 99%